Rapid response computed tomography reporting protocol for stroke fast track in Phrae hospital - ศิริยา บุษยรัตน์; มะโนยานะ นัฏกานท์; ถือแก้ว จรวยพร; เขตสมัคร รัฐธิกาล (Journal of Health Science of Thailand, 2025)
The purpose of this study was to assess the outcomes of rapid response reporting protocol for stroke fast track in Phrae hospital compare with original practice. This study was a historical controlled study. The sample was 202 acute stroke patients who enter stroke fast track protocol during October 2023 to May 2024. Retrospective review of 101 patients who received original practice and prospective study another 101 patients who receive new develop rapid response reporting protocol, using rapid CT report form and ASPECTS/pc-ASPECTS check list form. Data were summarized by descriptive statistics, to analyze difference between groups using Fisher exact test, t-test and rank-sum test, to analyze outcomes of rapid response reporting service using linear regression, p < 0.05 was considered as statistically significant. It was found that the rapid response reporting protocol for stroke fast track significantly reduced CT initiation to CT interpretation time for 7.2 minutes (95% CI -9.6, -4.8, p-value < 0.001), door to CT time for 8.7 minutes (95% CI -12.9, -4.5, p-value < 0.001) and door-to-needle time for 15.9 minutes (95% CI -27.2, -4.6, p-value 0.006) and increased the patient who received rtPA in 60 minutes from 36.8% to 63.0% (p-value 0.034). We conclude that rapid response reporting protocol should be favorable strategy to improve door-to-needle time for acute stroke patients in stroke fast track in Phrae hospital.